The Application of Principal Component Analysis and the Wilson Model in Urban Economics - Yiwei Chen; Congbin Guo; Junhao Fu (Mathematics)
This article first selects the “Urban Statistical Yearbook” data of 264 prefecture-level cities in China from 2004 to 2018 as the raw data, and uses principal component analysis and the Wilson model to calculate the spatial information diffusion capacity of each prefecture-level city. The correlation analysis between industrial agglomeration, spatial information diffusion capacity, and urban economic resilience is verified, and this article provides reference materials for the specific application of principal component analysis and the Wilson model in urban economics.